Process management in spinning - Kumar, R. Senthil (Boca Raton : CRC Press, 2015)
This book gives a broad outlook on various aspects of process management from mixing to winding department. Raw material evaluation and selection plays a vital role in process control of spinning. It describes the scientific method adopted to optimize raw material properties. The influence of machine components on process control and quality in each department are covered in a detailed manner with charts and data wherever necessary--
1. Process control in mixing -- 2. Process control in blow room -- 3. Process control in carding -- 4. Process control in drawing -- 5. Process control in comber and its preparatory -- 6. Process control in speed frame -- 7. Process control in ring spinning -- 8. Process control in winding -- 9. Process control in rotor spinning -- 10. Energy management in the spinning mill -- 11. Humidification and ventilation management -- 12. Pollution management in spinning mill -- 13. Process management tools -- 14. Productivity, waste management, and material handling -- 15. Case studies.
Keywords: Spinning; Process control